Optimisation of ring seine using large meshsections - a theoretical approach - Edwin, Leela; Hridayanathan, C (Indian Journal of Fisheries, 2014)
The introduction of the ring seine in the mid eighties in the artisanal marinefisheries sector of Kerala helped the traditional fishermen to counter themarginalisation felt due to the emergence of the large mechanized sector to acertain extent. This communication is based on the theoretical consideration toreduce the weight of this huge gear by introducing large mesh section in thewing region. The reduction brought about in the total weight of webbing bysubstituting with large mesh knotless webbing and the cost of fabrication of thering seine was estimated. Two hypothetical cases were taken for calculation. Inthe first case when three panels from both wings were substituted effecting a4% reduction in weight and 2.6% reduction in cost and in the second case wherethe last eight panels were substituted with large mesh effecting 14% reductionin weight and 7.3% reduction in cost. The reduced weight will consequentlyreduce the size of the craft and the horse power of the engine and thereby the operational costs.